First-line treatments for extensive-stage small-cell lung cancer with immune checkpoint inhibitors plus chemotherapy: a China-based cost-effectiveness analysis - Yi, Lidan; Zhou, Zhen; Zeng, Xiaohui; Tan, Chongqing; Liu, Qiao (Frontiers in Immunology, 2024)
Objective: To determine the cost-effectiveness of imported immune checkpoint inhibitors (ICIs) such as atezolizumab and durvalumab, and domestic ICIs like serplulimab and adebrelimab, in combination with chemotherapy for extensive-stage small cell lung cancer (ES-SCLC) in China.Methods: Using a 21-day cycle length and a 20-year time horizon, a Markov model was established to compare the clinical and economic outcomes of five fist-line ICIs plus chemotherapy versus chemotherapy alone, as well as against each other, from the perspective of the Chinese healthcare system. Transition probabilities were estimated by combining the results of the CAPSTONE-1 trial and a published network meta-analysis. Cost and health state utilities were collected from multiple sources.Both cost and effectiveness outcomes were discounted at a rate of 5% annually. The primary model output was incremental cost-effectiveness ratios (ICERs). A series of sensitivity analyses were preformed to assess the robustness of the model.In the base-case analysis, the addition of first-line ICIs to chemotherapy resulted in the ICERs ranged from 80,425.31/QALY to 812,415.46/QALY, which exceeded the willing-to-pay threshold set for the model. When comparing these first-line immunochemotherapy strategies, serplulimab plus chemotherapy had the highest QALYs of 1.51286 and the second lowest costs of 60,519.52, making it is the most cost-effective strategy. Our subgroup-level analysis yielded results that are consistent with the base-case analysis. The sensitivity analysis results confirmed the validity and reliability of the model.In China, the combination of fist-line ICIs plus chemotherapy were not considered cost-effective when compared to chemotherapy alone. However, when these fist-line immunochemotherapy strategies were compared with each other, first-line serplulimab plus chemotherapy consistently demonstrated superiority in terms of cost-effectiveness. Reducing the cost of serplulimab per 4.5 mg/kg would be a realistic step towards making first-line serplulimab plus chemotherapy more accessible and cost-effective.